2004
DOI: 10.1165/rcmb.2003-0425oc
|View full text |Cite
|
Sign up to set email alerts
|

Respirable Coal Dust Particles Modify Cytochrome P4501A1 (CYP1A1) Expression in Rat Alveolar Cells

Abstract: Cytochrome P4501A1 (CYP1A1) metabolizes polycyclic aromatic hydrocarbons in cigarette smoke to DNA-binding reactive intermediates associated with carcinogenesis. Epidemiologic studies indicate that the majority of coal miners are smokers but have a lower risk of lung cancer than other smokers. We hypothesized that coal dust (CD) exposure modifies pulmonary carcinogenesis by altering CYP1A1 induction. Therefore, male Sprague Dawley rats were intratracheally instilled with 2.5, 10, 20, or 40 mg CD/rat or vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…In addition also other investigators reported about the potential of DEPM to interfere with the expression level of Cyp1a1 in rat alveolar cells [53]. Others speculated that such a downregulation after exposure to exhaust components could represent a cytoprotective response [54], preventing the cells from toxic metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In addition also other investigators reported about the potential of DEPM to interfere with the expression level of Cyp1a1 in rat alveolar cells [53]. Others speculated that such a downregulation after exposure to exhaust components could represent a cytoprotective response [54], preventing the cells from toxic metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, only scant information is available on the effects of inflammation on extrahepatic P450 expression. One study showed that downregulation of CYP1A1 in the lung is associated with inflammation (Ghanem et al, 2004). In another study, lipopolysaccharide was found to induce CYP2E1 in astrocytes via C/EBP ␤ and ␦ binding sites in the CYP2E1 promoter (Kelicen and Tindberg, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin-embedded sections of the left lung lobe were used for immunofluorescent detection of cytokeratin-8/18. After xylene deparaffinizating, cytokeratin-8/18 staining was done by the procedure described by Ghanem et al (11). A polyclonal guinea pig anticytokeratin-8/18 was used as the primary antibody (Research Diagnostics, Flanders, NJ), and an FITC-labeled donkey anti-guinea pig IgG (Research Diagnostics) was used as the secondary antibody to detect cytokeratin.…”
Section: Methodsmentioning
confidence: 99%